A feasibility study for the introduction of micro-enema to improve organ consistency in patients receiving radiotherapy for urinary bladder cancer. Issue 1 (20th June 2017) - Hutton, D.; Callender, J.; Hutton, N.; Wong, H.; Syndikus, I.
Abstract: Aims: The aim of the study was to assess the effect on rectal consistency, of introducing a micro-enema in the preparation of patients receiving radiotherapy treatment of urinary bladder cancer. Materials and methods: The treatment cone beam computed tomography (CBCT) images from patients receiving radiotherapy for bladder cancer were retrospectively assessed. CBCT datasets from nine patients treated without rectal preparation (97 CBCT), and 13 patients (134 CBCT) treated following micro-enema use before planning and treatment were evaluated. CBCT were compared with the planning computed tomography for rectal status, rectal diameter and presence of gas. Results: Reproducibility of an empty rectum was achieved in 70% of treatment fractions delivered using an enema protocol compared with 33% of fractions delivered without preparation. In total, 10% of fractions were delivered with the presence of faeces or faeces and gas, compared with 46% of fractions for the non-intervention group. Enemas did not affect the proportion of fractions delivered with gas, however, where gas was present, 65% of CBCT fractions had <5% gas for patients using enemas compared with 32% without. Findings: The use of a micro-enema before planning scan and each fraction was well tolerated and proved effective in managing and reducing inter-fraction variations in rectal volume and contents.